2013
DOI: 10.1097/ico.0b013e318298e176
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Descemet Corneal Dystrophy and X-Linked Ichthyosis Associated With Deletion of Xp22.31 Containing the STS Gene

Abstract: Purpose To report the association of X-inked ichthyosis and pre-Descemet corneal dystrophy with a deletion of the steroid sulfatase gene (STS) detected with microarray-based comparative genomic hybridization (aCGH). Methods A slit lamp biomicroscopic and cutaneous examination were performed, after which a saliva sample was collected as a source of genomic DNA. PCR amplification of each of the 10 exons of STS was performed, as was aCGH on genomic DNA to detect copy number variation (CNV). Results Slit lamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The percentage of cryptorchidism in our patients (12.9%) is in line with the literature findings in XLI, while the absence of corneal opacities can be explained by their young age. Indeed, the detection of corneal opacities is quite rare before puberty . Nine of 33 patients (27%) presented manifestations of ADHD, confirming recent literature findings on the increased prevalence of these behavioural phenotypes in XLI .…”
Section: Discussionsupporting
confidence: 81%
“…The percentage of cryptorchidism in our patients (12.9%) is in line with the literature findings in XLI, while the absence of corneal opacities can be explained by their young age. Indeed, the detection of corneal opacities is quite rare before puberty . Nine of 33 patients (27%) presented manifestations of ADHD, confirming recent literature findings on the increased prevalence of these behavioural phenotypes in XLI .…”
Section: Discussionsupporting
confidence: 81%
“…So we speculated that his mother and his maternal mother were heterozygous females, and the STS gene deletion of our patient was hesitated from them. Hung et al [ 19 ] also demonstrated that the corneal changes in PDCD and X-linked ichthyosis were associated with deletion of the STS detected with microarray-based comparative genomic hybridization. STS is found throughout the body, including the epidermis, where it is thought to play a role in the steroid production and lipid regulation of the stratum corneum [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As steroid sulfatase deficiency leads to elevated plasma levels of cholesterol sulfate, corneal opacities are thought to represent focal accumulations of cholesterol sulfate 40. Hung et al 44 have reported a case of pre-Descemet corneal dystrophy associated with XLI in which the diagnosis was confirmed by identification of a deletion of the steroid sulfatase gene. However, corneal deposits do not occur in all patients even with raised levels of cholesterol sulfate 35 37 45.…”
Section: Ophthalmic Featuresmentioning
confidence: 99%